Exercise and inflammation in coronary artery disease: A systematic review and meta-analysis of randomised trials. Issue 7 (2nd April 2020) - Thompson, Gareth; Davison, Gareth W.; Crawford, Jacqui; Hughes, Ciara M.
ABSTRACT: Current evidence suggests that chronic inflammation contributes to the development of coronary artery disease (CAD). Interestingly, exercise may constitute a method of reducing inflammation in this patient population. As such, this systematic review and meta-analysis examined the evidence generated by randomised studies that investigated the effect of exercise on inflammatory biomarkers in CAD. Literature was sought from various sources. Outcomes were pooled in a random-effects model to calculate standardised mean differences (SMD) with 95% confidence intervals (CI). Twenty-five studies were reviewed; post-intervention C-reactive protein (SMD: −0.55 (95% CI: −0.93, −0.16), P = 0.005), fibrinogen (SMD: −0.52 (95% CI: −0.74, −0.29, P = <0.00001)), and von Willebrand factor (SMD: −1.57 (95% CI: −2.23, −0.92), P = <0.00001) values were significantly lower in exercise groups compared to controls. In addition, qualitative analyses identified evidence that supports a beneficial effect of exercise on these acute-phase reactants. However, the impact of exercise on anti–inflammatory cytokines, adhesion molecules, and chemokines is equivocal, which may be attributed to a paucity of research. Nevertheless, the findings of this review suggest that exercise induces an anti–inflammatory effect in CAD patients. Although, the quality of evidence needs to be improved by further randomised studies with high methodological qualities and large sample sizes.